Tor Hidden Services Discovery and Analysis: A Literature Survey. Issue 1 (January 2021) - Bian, Jingjing; Cao, Chunjie; Wang, Longjuan; Ye, Jun; Zhao, Yan; Tang, Chaosheng
Abstract: Hidden services are a feature of Tor(The Onion Router)[1]. It provides anonymity for the service requester while maintaining the anonymity of the service provider. Since it is quite difficult to trace back and locate both parties in the communication, the criminals use hidden services mechanisms to construct various illegal activities in the darknet, which has brought adverse effects to society. In order to prevent the abuse of Tor hidden services, the discovery and analysis of hidden services are particularly important. The aim of this survey paper is to review and compare the literature of the past five years, provide the readers with methods for discovering tor hidden services, along with the various content analysis methods developed and proposed from time to time. we explain their key ideas and show their interrelations.